Social Marketing - Awareness and Satisfaction Levels of Government Aided Health Insurance Project in Rural Tamil Nadu - Swaminathan, T. N.; Viswanathan, P. K. (Indian Journal of Marketing, 2015)
In developing countries, one of the contexts of social marketing is to foster the use of various health-related products and services independent of many non-governmental organizations (NGOs) and donors from developed countries, who have largely funded and devised social marketing activities in these countries. These activities have also been taken up by local organizations - state owned, state supported, and private. In India, there is a growing demand for quality medical care due to the poor quality of state owned hospitals, increase in lifestyle diseases, increasing private health care costs, and cost of medicines. This makes health insurance a necessity today more than a luxury. To mitigate the problem of quality health care at affordable costs, there are state interventions, the notable ones being Yeshasvini of Karnataka, Arogyasri of Andhra Pradesh, and Chief Minister’s Comprehensive Health Insurance Scheme of Tamil Nadu. The Chief Minister’s Comprehensive Health Insurance Scheme is one of the innovative health insurance schemes introduced by the Tamil Nadu Government for below poverty line (BPL) families, covering a population of 14 million with an annual income of INR 72000 (USD 1400 ; 1 USD = 50 INR in 2009 ) or less. The scheme has been implemented through 663 hospitals (20 public sector hospitals and 643 private hospitals). This scheme assures treatment and saves the lives of people from 51 types of diseases. This study aimed at studying the public-private partnership in health care with specific reference to the Chief Minister’s Comprehensive Health Insurance Scheme of the Tamil Nadu government in terms of awareness, satisfaction, and impact through qualitative and quantitative research methodologies. The study indicated that the awareness of the respondents about this scheme was poor, but was significantly better amongst those who had availed this scheme. The satisfaction levels measured among the respondents, who had used this scheme at least once, clearly indicated that the people were satisfied with the overall implementation of the scheme, the services/facilities provided by the hospitals, and the treatment rendered by them.